Risk and Prognosis of Hepatocellular Carcinoma in Mexican Americans with Type 2 Diabetes Mellitus - Hatia RI; Hwang LY; Li R; Troisi C; Jalal PK; Amos CI; Gomez HF; Chun YS; Rashid A; Kaseb AO; Scheet PA; Hassan MM (Journal of Hepatocellular Carcinoma)
Rikita I Hatia,1 Lu-Yu Hwang,2 Ruosha Li,3 Catherine Troisi,4 Prasun K Jalal,5 Christopher I Amos,6 Henry F Gomez,1 Yun Shin Chun,7 Asif Rashid,8 Ahmed O Kaseb,9 Paul A Scheet,1 Manal M Hassan1 1Department of Epidemiology, The University of Texas MD Anderson Cancer Center, Houston, TX, USA; 2Department of Epidemiology, School of Public Health, The University of Texas Health Science Center at Houston, Houston, TX, USA; 3Department of Biostatistics and Data Science, School of Public Health, The University of Texas Health Science Center at Houston, Houston, TX, USA; 4Department of Management, Policy & Community Health, School of Public Health, The University of Health Science Center at Houston, Houston, TX, USA; 5Department of Gastroenterology and Hepatology, Baylor College of Medicine, Houston, TX, USA; 6Institute for Clinical and Translational Research, Baylor College of Medicine, Houston, TX, USA; 7Department of Surgical Oncology, The University of Texas MD Anderson Cancer Center, Houston, TX, USA; 8Department of Pathology, The University of Texas MD Anderson Cancer Center, Houston, TX, USA; 9Department of Gastrointestinal Medical Oncology, The University of Texas MD Anderson Cancer Center, Houston, TX, USACorrespondence: Manal M Hassan, Department of Epidemiology, Unit 735, The University of Texas MD Anderson Cancer Center, 6900 Fannin Street, Houston, TX, 77030, USA, Tel +1-713-794-5452, Email mhassan@mdanderson.org Lu-Yu Hwang, Department of Epidemiology, School of Public Health, The University of Texas Health Science Center at Houston, 1200 Pressler Street, RAS E717, Houston, TX, 77030, USA, Tel +1-713-500-9384, Email lu-yu.hwang@uth.tmc.eduIntroduction: Hepatocellular carcinoma (HCC) disproportionately affects Hispanic persons with higher age-specific incidence and increased mortality rates compared to non-Hispanic Whites. These high rates of incidence and mortality may be explained by the variation in risk factors. Given the high prevalence of type 2 diabetes mellitus (DM) among the Hispanic population, we aimed to assess the risk and prognosis of HCC in Mexican Americans with type 2 DM with consideration of treatment for DM.Methods: A case-control study of 241 Mexican American HCC patients and 500 healthy controls in Texas was conducted. Multivariable logistic regression analysis was performed to determine the association between type 2 DM and HCC risk while adjusting for other risk factors. Also, a restricted analysis of patients with type 2 DM was conducted to determine the effects of age at onset and duration of DM on HCC risk. Interactions among DM, heavy alcohol consumption, and viral hepatitis infection were examined. Overall survival was examined, and multivariable Cox proportional hazards regression analysis was performed for HCC patients with type 2 DM.Results: The adjusted odds ratio (AOR) for DM was 2.74 (P < 0.01). Compared with patients who had DM for 2– 10 years, those who had it for at least 20 years had an AOR of 4.60 (P = 0.04). Metformin use was associated with a reduced risk of death in HCC cases with type 2 DM, with a hazard ratio of 0.72 (P = 0.01) as compared with non-users.Conclusion: Our results demonstrate that type 2 DM was independently associated with increased risk of HCC among Mexican Americans. Metformin use was associated with improved survival among HCC patients with type 2 DM. Type 2 DM significantly increased the risk of HCC alone and in conjunction with other parameters of metabolic syndrome in the Mexican American population after adjusting for other risk factors.Keywords: diabetes mellitus, Mexican Americans, hepatocellular carcinoma, metformin, interactions